Green Economy, Technology, People and Industrial Tourism (Get Points) - Natita, Rendi Kusuma; Septiarini, Eka; Abdullah, Riono Aulia (Research Collaboration Community (RCC), 2025)
Rapid technological and economic advancement has resulted in the proliferation of environmentally detrimental products and consumption patterns, significantly impacting the environment. Plastic pollution has emerged as a critical environmental concern, with Indonesia ranking fifth among the world's largest plastic waste producers. Annually, Indonesia generates approximately 7.8 million tons of plastic waste, of which 4.9 million tons are inadequately managed. For an extended period, Indonesia relied on a linear economic model characterized by a